The Role of the Village Head in Efforts yo Increase Community Participation in Mutiara Laut Village, Tomilito District, North Gorontalo Regency - Wienda Pararang; Ellys Rahman; Sofyan Al Hadar (MultiTech Publisher, 2023)
The purpose of this study is to obtain an overview of the role of the village head in efforts to increase community participation in Mutiara Laut Village, Tomilito District, North Gorontalo Regency. This research is qualitative research with descriptive methods. The location of this research is in Mutiara Laut Village, Tomilito District, North Gorontalo Regency. The research to be carried out uses 2 (two) types of data sources, namely: Primary Data and Secondary Data. Data collection techniques used in this study are: observation, interviews, anddocument review. Data Analysis techniques used are data reduction, data presentation, and conclusions. The results showed that the role of the Village Head in efforts to increase community participation in Mutiara Laut Village, Tomilito District, North Gorontalo Regency has not been optimal, because the implementation of the development program still has problems in the field that should be evaluated.